Evolution of endodontic medicine: a critical narrative review of the interrelationship between endodontics and systemic pathological conditions - Cintra, Luciano Tavares Angelo [UNESP]; Gomes, Maximiliano Schünke; da Silva, Cristiane Cantiga [UNESP]; Faria, Flávio Duarte [UNESP]; Benetti, Francine; Cosme-Silva, Leopoldo; Samuel, Renata Oliveira; Pinheiro, Tiago Novaes; Estrela, Carlos; González, Alvaro Cruz; Segura-Egea, Juan José (Springer Nature, 2021)
Endodontics has gained emphasis in the scientific community in recent years due to the increase in clinical and in animal models studies focused on endodontic medicine, which aims to evaluate the interrelationship between systemic and periapical tissues pathological conditions. These studies have shown that systemic changes can boost the pathogenesis of endodontic infection, favoring its development and progression. A contrary relationship is reported in numerous studies that affirm the potential of endodontic infection to trigger systemic damage and may lead to the worsening of pre-existing pathologies. Recently, the potential of filling materials to develop systemic changes such as neurological alterations had been evaluated, also showing that systemic diseases can negatively influence tissue responses to filling materials after endodontic treatment. Despite advances in endodontic medicine studies, there are still gaps in knowledge on the mechanisms of interactions between apical periodontitis (AP) and systemic diseases and much research to be done. In this sense, this critical narrative literature review aimed to show the evolution of studies in endodontic medicine to help the endodontist to know the role of systemic diseases in the pathogenesis of AP and the possible interference in the repair of periapical tissues after endodontic treatment, as well as to evidence the systemic complications that can be triggered or aggravated in the presence of endodontic infection.
Keywords: Apical periodontitis; Dental pulp necrosis; Endodontic; Oral health; Root canal filling materials